Concept of Business Ethics in Islam - Approach to the Entrepreneur - Zulkifli, Che Mohd; Saripuddin, Che Omar Ana Siti Sarpina (Journal of Asian Business Strategy, 2015)
Identified entrepreneurship as a catalyst and the largest contributor to the economic development of a country. Islam always encourages its followers to involve in the business from day one. A business activity as a worship will encourage a Muslim to become a successful entrepreneur in this world and the hereafter. Even so, there are Muslim entrepreneurs who conduct business regardless of the meaning lawful or unlawful in Islamic side. They do business in a way wrong (unethical) to provided good returns. The concept of business ethics in Islam can make a conscious entrepreneur. Entrepreneurs who fear will always be steadfast in order to realize entrepreneurial comprehensively and according to Islamic law. Therefore, every entrepreneur should continuously practiced Islam based on the Qur’an and Sunnah and always resourceful, fair, honest, trustworthy and sincere in every business establishment conducted to high ethical values among entrepreneurs.